The Golden Calf between Bible and Qurʾan: Scripture, Polemic, and Exegesis from Late Antiquity to Islam: (by Michael E. Pregill) (American Journal of Islam and Society, 2025)
Michael Pregill’s The Golden Calf between Bible and Qurʾan draws from Jewish, Christian, and Muslim sources to understand how the story of the Israelites worshipping the Golden Calf has been understood across scriptural communities. This book marks the first time that the story has been the subject of a comprehensive comparative treatment. Drawing from Arabic, Aramaic, and Hebrew primary and exegetical sources, Pregill seeks to revive the earliest approach of Western scholarship towards the Qurʾan, that it should be understood as Biblical literature, or rather, late antique religious discourse. To this end, Pregill argues that the story’s employment in both the Hebrew Bible and the Qurʾan can be understood as a “continuities of discourse” rather than a communication of specific influences.